Increased incidence of cervical cytological abnormalities in women with genital warts or contact with genital warts: a need for increased vigilance?. Issue 6 (December 1991) - Rowen, D; Carne, C A; Sonnex, C; Cooper, P
Abstract : OBJECTIVE–To determine whether women who have a history of genital warts or whose sexual partners have such a history were more likely to have borderline or dyskaryotic cervical smears than other women. DESIGN–Prospective study conducted over a five month period. SETTING–A genitourinary medicine clinic in Cambridge, UK. PATIENTS–One hundred and eighty five women who attended the clinic during the study period, on whom cervical cytology was performed. Ninety-seven had a history of genital warts and twenty had partners with genital warts. METHODS–Cervical cytology taken by standard methods. Demographic data and sexual history obtained by questionnaire. Colposcopy was performed on patients with a history of warts or wart contact. OUTCOME MEASURED–Relative incidence of cytological abnormalities in the various groups of patients. RESULTS–"Borderline" nuclear change was the most frequent abnormality reported in the wart contact group (six cases) whereas mild dyskaryosis was the most frequent abnormal finding in those women with a history of warts (21 cases). CONCLUSIONS–Women with warts or contact with genital warts were more likely to have borderline or dyskaryotic cervical smears than women without such a history. Recommendations for follow-up of these patients are made.